Clock Synchronization Technique- A Review - Iqbaljeet,; Rana, Sonal (International Journal of Computer Sciences and Engineering, 2025)
The wireless network uses the communication protocols and it uses the air through the operation of the communication protocols. Wireless networks use a carrier sense protocol for the synchronization and these protocols are similar to the Ethernet standard. In this paper we have reviewed CSMA and RFID protocol. CSMA/CA is Carrier Sense Multiple Access/Collision avoidance protocol for carrier transmission in 802.11 networks. RFID is an enhancement of CSMA protocol. By using RFID protocol, collision and packet loss problem can be controlled.